Federal University of Campina Grande Center of Technology and Natural Resources post-graduate programing engineering and management of natural resources – PPGEGRN: ISBN 978-630-95064-8-1 - Oliveira, Zenon Sabino de (Technium Books, 2025)
The book: Federal University of Campina Grande Center of Technology and Natural Resources post-graduate programing engineering and management of natural resources – PPGEGRN is published in Technium. This content was translated by Stella Park. Any suggestions concerning the book’s content may be sent to stellamaypark357@gmail.com